2015
DOI: 10.4103/0189-6725.172566
|View full text |Cite
|
Sign up to set email alerts
|

A review of cleft lip and palate management: Experience of a Nigerian Teaching Hospital

Abstract: Background:Cleft lip (CL) and palate (CLP) management is multidisciplinary. A cleft team was formed in a Nigerian Tertiary Hospital to address the health needs of cleft patients in the centre.Aim:This paper aims at documenting the Aminu Kano Teaching Hospital (AKTH) management protocol for orofacial clefts and also to review our experience with CLP surgeries performed at AKTH since our partnering with Smile Train.Materials and Methods:A retrospective review of all the cleft patients surgically treated from Jan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Longer hospital stays are associated with increased risk of complications and resource utilization, with the additional newfound risk of potential exposure to COVID-19. Efunkoya et al 35 reported that patients remain in the hospital for 7 days after cleft lip and palate repair for monitoring in a Nigerian teaching hospital. Hush et al 29 found that the length of hospital stay after cleft palate repair has reduced from 1.83 to 1.16 days following implementation of ERAS protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Longer hospital stays are associated with increased risk of complications and resource utilization, with the additional newfound risk of potential exposure to COVID-19. Efunkoya et al 35 reported that patients remain in the hospital for 7 days after cleft lip and palate repair for monitoring in a Nigerian teaching hospital. Hush et al 29 found that the length of hospital stay after cleft palate repair has reduced from 1.83 to 1.16 days following implementation of ERAS protocol.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 11 12 13 14 15 ] CLA was the most common diagnosis made which concur with previous local studies which also showed a similar trend. [ 15 16 ] Other authors have however reported CL and palate to be more prevalent in their centers. [ 17 18 19 20 ] Furthermore, similar to previous studies, we found unilateral clefts occurring more often on the left than the right side.…”
Section: Discussionmentioning
confidence: 99%
“…Many surgical techniques have been advocated to improve the result of cleft surgery. 7 It is obvious that every surgeon attempts to prevent complications following these surgical procedures. However, the surgeon may be trapped unwittingly into some pitfalls.…”
Section: Discussionmentioning
confidence: 99%
“…Collected data included age, sex, type of cleft, and types of complication associated were analyzed using Statistical Package for Social Sciences (SPSS) for windows student version 13.0 (SPSS Inc., Chicago, IL, USA). 7 Statistical significance was inferred at P < 0.05.…”
Section: Methodsmentioning
confidence: 99%